(untitled) (Dermatology Reports, 2024)
Riehl’s melanosis (RM) is a pigmentary disorder more common in individuals with dark skin phototypes. It is considered a form of pigmented contact dermatitis. In this paper, we present a case of RM due to the rubber component of a work facial mask, in which dermoscopy and patch test were the most important tools to help physicians diagnose. In addition, we reviewed the main dermoscopic clues that may be useful in differential diagnosis with other facial pigmentary disorders.